Antioxidant properties of methanolic extract of Canarium odontophyllum fruit - Azlan, Azrina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
The antioxidant properties of skin, flesh and kernel of Canarium odontophyllum fruit were determined. The methanolic extracts of the fruit were screened for their total phenolic content and antioxidant properties. The averaged antioxidant properties (mM TE/g FM) in skin, flesh, and kernel of Canarium odontophyllum were 16.46 ± 0.24, 20.54 ± 0.35, and 8.89 ± 0.29, respectively by DPPH assay; 151.24 ± 9.75, 70.58 ± 2.98, and 5.65 ± 0.02, respectively by FRAP assay; and 47.9 ± 0.00, 11.61 ± 1.14, and 3.00 ± 0.00, respectively by β-Carotene bleaching method. The averaged OH scavenging activity (mg DMSOE/mg FM) in skin, flesh, and kernel of Canarium odontophyllum were 43.33 ± 13.85, 7.81 ± 1.42, and 3.31 ± 0.80, respectively. While averaged total phenolic content (mg GAE/100g FM) were 387.5 ± 33.23, 267.0 ± 4.24, and 51.0 ± 0.00 for skin, flesh, and kernel respectively. Antioxidant activities were positively correlated with the total phenolic content (0.71 ≤ r ≤ 0.84).